MORBIDITY PATTERNS OF PATIENTS ATTENDING PSYCHITARY OPD IN TERTIARY CARE HOSPITAL IN AHMEDABAD - Nayak, Sunil; Sonaliya K N (National Journal of Medical Research, 2011)
Objective: To find out the common psychiatric disorders among patients attending psychiatry OPD and also to study the role of factors like age, sex, education and occupation, marital status and various precipitating factors on mental health status of the patients. Study Design: Cross Sectional Study. Methods: A total of 200 patients were studied in a period of two months (April-July ’08). Patients attending psychiatry OPD were examined with the help of a trained psychiatrist. Information regarding the patients was taken using pre-designed structured proforma. Diagnosis was made by trained psychiatrist based on ICD-10 classification in regard to DSM IV criteria. Results: Majority of psychiatric patients (27.8 %) belonged to age group 20-29 years and above 49 years in 25.5 % cases, most of them were males (59.9 %). Occupational analysis showed that more number of psychiatric patients (32%) belonged to labourer group followed by unemployed (26%). 39% of patients belonged to class IV, Modified Prasad’s Classification and in 12.5 % cases psychiatric problems were precipitated by poor financial condition. Psychiatric problems were more in illiterates (28%) and majority of the patients (65.5%) were married. In 46% cases patients were suffering from various health related problems and 12 % of patients consumes alcohol. The morbidity pattern showed that majority were affected by depression (29%), schizophrenia (18%) and substance abuse psychiatric disorder (11%).